Progress in absorbable polymeric thread used as acupoint embedding material. (September 2021) - Zhao, Jinrong; Wang, Mingming; Xu, Jun; Yang, Ying
Abstract: Acupoint embedding therapy is a treatment that embeds absorbable thread into target acupoints, so as to provide continuous stimulation to acupoints and to replace retained acupuncture. Many types of absorbable threads are available and generally can be divided into natural and synthetic polymers according to the source of material. According to the literature, the threads currently used in acupoint embedding have some limitations, and may cause side effects in clinical practice. Bioactive threads may be used to further reduce side effects and promote application of acupoint embedding. Highlights: Acupoint embedding provides sustainable stimulation and replaces retained acupuncture. Absorbable natural and synthetic polymeric threads are available for embedding. Catgut, chitosan, PLGA and PDS threads have limitations and may cause side effects. Bioactive threads may reduce side effects and further researches are granted.